1986
DOI: 10.1093/carcin/7.1.33
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of mouse epidermal cell lipoxygenase by flavonoids: structure—activity relationships

Abstract: Lipoxygenase was extracted from mouse epidermal cells and partially purified by ammonium sulfate precipitation. Using a biological oxygen monitor for activity measurements and linoleic acid as substrate, the effect of a series of flavonoids on lipoxygenase activity was determined. Flavone itself did not inhibit lipoxygenase, but hydroxylated derivatives retaining the double bond in the 2,3 position and having a hydroxyl group in the 3 position (such as quercetin and 3-hydroxy-flavone) were potent lipoxygenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Their effects on bacteria-derived enzymes is less well documented. Flavones and flavonols, which possess the C2-C3 double bond [Wheeler and Berry, 1986;Ferriola et al, 1989;Merlos et al, 1991;Eaton et al, 1996], have been considered the main flavonoids related to the inhibition of enzymes. Among them, quercetin, galangin, kaempferol, kaempferide (flavonols) and chrysin, apigenin, and acacetin (flavones) were identified in the EEPs tested in the present study Koo et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Their effects on bacteria-derived enzymes is less well documented. Flavones and flavonols, which possess the C2-C3 double bond [Wheeler and Berry, 1986;Ferriola et al, 1989;Merlos et al, 1991;Eaton et al, 1996], have been considered the main flavonoids related to the inhibition of enzymes. Among them, quercetin, galangin, kaempferol, kaempferide (flavonols) and chrysin, apigenin, and acacetin (flavones) were identified in the EEPs tested in the present study Koo et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Flavones and flavonols, which have an unsaturated double bond between positions C-2 and C-3 (Table 1), showed remarkable inhibition of GTF activity; in contrast, flavanones and dihydroflavonols, which lack a double bond between C-2 and C-3, exhibited only modest inhibitory activities. Results from previous studies have shown that flavones and flavonols are the main flavonoids related to inhibition of several mammalian enzymes, which suggests that a double bond between C-2 and C-3 is required for inhibitory effects (15,52). The presence of a double bond between C-2 and C-3 may provide a site for nucleophilic addition by side chains of amino acids in GTFs.…”
Section: Vol 46 2002 Biological Effects Of Propolis Compounds 1305mentioning
confidence: 98%
“…The effect of n-PG, NDGA and SHAM was related to their antioxidant activity; these compounds are supposed to act as free radical scavengers, inhibiting all types of oxygenases. Flavonoid compounds such as esculetin (6,7-dihydroxycoumarin), quercetin (3,3',4',5,7-pentahydroxyflavone) and flavonol (3-hydroxyflavone) have been reported to inhibit lipoxygenase and cyclooxygenase in animal cells (Wheeler and Berry, 1986) with a strong structure-activity relationship. Only esculetin and quercetin inhibited tobacco lipoxygenase; the same specificities have been reported for soybean lipoxygenase (Wheeler and Berry, 1986).…”
Section: Characterization Of Lipoxygenase Inhibitorsmentioning
confidence: 99%
“…Flavonoid compounds such as esculetin (6,7-dihydroxycoumarin), quercetin (3,3',4',5,7-pentahydroxyflavone) and flavonol (3-hydroxyflavone) have been reported to inhibit lipoxygenase and cyclooxygenase in animal cells (Wheeler and Berry, 1986) with a strong structure-activity relationship. Only esculetin and quercetin inhibited tobacco lipoxygenase; the same specificities have been reported for soybean lipoxygenase (Wheeler and Berry, 1986). Anti-inflammatory drugs such as indomethacin, salicylic acid, ibuprofen, mefenamic acid and piroxicam, which inhibit cyclooxygenase enzymes and soybean lipoxygenase (Sircar et al, 1983), did not inhibit tobacco lipoxygenase, even at concentrations much higher than the lCso reported for soybean lipoxygenase.…”
Section: Characterization Of Lipoxygenase Inhibitorsmentioning
confidence: 99%